Acesso aos serviços na atenção à saúde da família em dois cenários da Bahia, Brasil: organização, modelo e participação social - Almeida, Márlon Vinícius Gama (2013)
The universal and equitable access is essential to analyze the relationship between the user and health services, as it provides the opportunity to host the man, individually and collectively, their entry into the system, in expressing their need for health, defense of equal rights and social justice, configuring it as an exercise to achieve citizenship. However, it is necessary to overcome reductionist link between access and "gateway", as commonly used, for achieving higher senses that portray as an instrument full of transformative possibilities of reality. This research aimed to discuss the organization of users' access to health services in family health and their interfaces with the model of health care in two scenarios of Bahia, Brazil, and analyze how social participation happens in the construction of collective demands for accessing health services in family health in those scenarios. Configured as a qualitative study, the number of subjects was defined by progressive inclusion, interrupted by saturation criterion. The study subjects were 102 people, distributed among three groups representing: group I (health team - 49), group II (USF users - 37) and group III (SUS municipal leaders - 16). Technical data collection: semi-structured and systematic observation. Method of analysis: thematic content analysis. The results show that the organization of access to family health occurs from scheduling demand or demand for free, while the latter refers to the urgent care and emergency mostly and the choice of marking model was agreed with users in community meetings. Many speeches converged on the difficulties that the lack of material resources and maintenance entail the construction of a universal access and quality. Much of the speech that brought the number of vacancies for additional tests and diagnostics, as well as consultations with experts, is insufficient and is far beyond the demand presented. From this perspective, the Health Councils arise within the conjuncture of popular participation and social control as a privileged place for listening to the community and the emergence of significant changes to society, though, only one respondent group II has demonstrated knowledge about the importance of social control and its potential is still very far from expected. Anyway, many times, we were awakened the sense that users had to go through a funnel to the realization of its entry in the health services, which represents the amount of barriers that need to be overcome in gaining entry into the system, although Many users can not, in practice, see their right to health care guaranteed.